FRI0168 ASSOCIATION OF OVERWEIGHT/OBESITY WITH IMPAIRED HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Gomez, A.; Butrus, F. H.; Johansson, P.; Åkerström, E.; Soukka, S.; Emamikia, S.; Enman, Y.; Pettersson, S.; Parodis, I.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) experience a considerably impaired health-related quality of life (HRQoL) compared with the general population. Previous literature has implied an association between high body mass index (BMI) and HRQoL diminutions. However, data are scarce and further exploration in large study populations and, importantly, with regard to the clinical significance of this association is needed. Objectives: The aim of this study was to determine whether overweight and/or obesity were associated with impaired physical and/or mental HRQoL aspects in the SLE population of two large clinical trials. Methods: We utilised pooled baseline data from the BLISS-52 (NCT00424476 ) and BLISS-76 (NCT00410384 ) clinical trials of belimumab (N=1684). Access to data was granted by GlaxoSmithKline. The patients were stratified into four groups based on their body mass index (BMI), according to WHO guidelines. We conducted comparisons between non-overweight versus overweight, and non-obese versus obese SLE patients. HRQoL was self-reported using the Medical Outcomes Study (MOS) short form 36 (SF-36) health survey, the functional assessment of chronic illness therapy (FACIT)-Fatigue scale and the three-level EuroQol- 5 Dimension (EQ-5D) questionnaire. We explored whether the differences in scores were clinically meaningful using previously determined thresholds for minimal clinically important differences (MCIDs). The non-parametric Mann-Whitney U test was used for comparisons between different BMI groups. Linear regression analysis was next applied to test independence in multivariable models, adjusting for age, sex, ethnicity, disease duration, disease activity, organ damage and standard of care treatment. Results: Forty-four per cent (44%) of the patients had a BMI score over the normal range, and 18% were obese. The overweight group performed worse than the non-overweight with regard to FACIT-Fatigue scores (mean ± standard deviation: 27.7 ± 12.1 vs 32.0 ± 11.3; P<0.001), EQ-5D score (0.70 ± 0.19 vs 0.76 ± 0.18; P<0.001) and all SF-36 subscales and component summaries. The differences were greater than the MCIDs for physical component summary (PCS) scores (36.9 ± 9.3 vs 40.8 ± 9.6; P<0.001), physical functioning (53.3 ± 25.1 vs 63.6 ± 25-1; P<0.001), role physical (48.0 ± 27.1 vs 55.6 ± 26.9; P<0.001), bodily pain (43.8 ± 22.4 vs 52.5 ± 25.1; P<0.001), vitality (39.6 ± 21.7 vs 46.6 ± 21.3; P<0.001), and social functioning scores (55.8 ± 25.2 vs 62.6 ± 25.2; P<0.001). Likewise, obese patients reported worse FACIT-Fatigue scores (25.7 ± 11.9 vs 31.1 ± 11.6; P<0.001), EQ-5D scores (0.68 ± 0.20 vs 0.75 ± 0.18; P<0.001) and clinically important diminutions of HRQoL in all SF-36 items, except for the mental component summary (MCS), role emotional and mental health. In multivariable linear regression analysis, the overweight and obese group showed worse PCS scores (standardised coefficient: β=-0.09; P<0.001 and β=-0.13; P<0.001, respectively) and FACIT-Fatigue scores (β=-0.11; P<0.001 and β=-0.10; P<0.001, respectively), and overweight patients had significantly impaired MCS scores (β=-0.05; P=0.039), irrespective of other factors. High disease activity and organ damage were associated with impaired HRQoL in all aspects, while Asian patients reported better PCS scores (and β=0.29; P=0.007) and FACIT-Fatigue scores (β=0.33; P=0.002). Conclusion: BMI above normal was highly associated with HRQoL impairment, especially in physical aspects. Further survey to examine causality is warranted to support structured weight control strategies as an intervention towards a more favourable HRQoL. Disclosure of Interests: None declared